2015
DOI: 10.1016/j.matdes.2015.02.011
|View full text |Cite
|
Sign up to set email alerts
|

A review of the behaviour and analysis of bolted connections and joints in pultruded fibre reinforced polymers

Abstract: This paper presents a literature review of the state-of-the-art experimental and analytical methodologies adopted in the construction industry for the design of mechanically fastened connections and joints in pultruded fibre reinforced polymer framed structures. Results and conclusions obtained from the published literature relating to the effects of critical parameters, which include geometry, material properties, configuration, connecting components, fasteners, lateral restraint, etc. on the mechanical behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(37 citation statements)
references
References 44 publications
0
30
0
3
Order By: Relevance
“…In this context, a great number of recent experimental research findings is available (Turvey and Wang, 2007;Girão Coelho et al, 2015a;2015b), as well as some numerical study on the effect of the joint behavior on the overall structural response (Minghini et al, 2009;.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, a great number of recent experimental research findings is available (Turvey and Wang, 2007;Girão Coelho et al, 2015a;2015b), as well as some numerical study on the effect of the joint behavior on the overall structural response (Minghini et al, 2009;.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, polymer composites have a prevalent use in a large range of infrastructure 2 including pipelines, utility poles, prefabricated pavements, renewable energy harvesting, chimneys or flues, rapidly deployable housing, decking for marine and naval structures and advanced retrofitting. Recent studies 3,4 have demonstrated that polymer composites, when designed appropriately, can provide a cost-effective alternative to current structural materials used for primary loading-bearing elements in civil infrastructure. Specific civil infrastructural applications of polymer composites include but are not limited to retrofitting of existing concrete structures, strengthening of steel structures, as internal reinforcing rods in reinforced concrete structures, in new construction as structural members 5 , in supporting frame structures 6 , multi-storey office 7 and residential buildings 8 , bridge decks for pedestrian and highway bridge superstructures 9 , electricity transmission towers 10 , and composite piles used for foundation construction 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Glass fiber‐reinforced plastic (GFRP), with many remarkable properties, such as high mechanical strength, lightweight, and high corrosion resistance, is used as structural material in the automobile, aerospace, architecture, and civil engineering fields . Mechanical and/or adhesive bonding are currently employed as bonding techniques to fabricate the complex GFRP products . Considering the damage to glass fibers in GFRP caused by mechanical processing, it seems that an adhesive bonding would be more suitable for a jointing GFRP.…”
Section: Introductionmentioning
confidence: 99%